Product management, controlling and logistics at agriculture and food manufacturing companies - Gál, József; Kmoskó, Éva (Jelenkori Társadalmi és Gazdasági Folyamatok, 2008)
How to understand logistics in agro-food business? Logistic activities considerably changed in the last few years. The original aim of satisfying quantity needs has been followed by the logistic activity which meets the market’s requirements, aims at satisfying the individual needs instead of standardized solutions, maximal the additional values, and finally, which gives a complex service. You can find special process of it in agriculture and food industry. These together mean a significant challenge for this profession. In our paper we try to understand methodology of logistics in agro-food business.